Microstructural Studies of Ag/TiO2 Thin Film; Effect of Annealing Temperature - A.R. Kamrosni; C.H. Dewi Suryani; A. Azliza; A.B.A. Mohd. Mustafa; M.S. Mohd. Arif Anuar; M. Norsuria; V. Chobpattana; L. Kaczmarek; B. Jeż; M. Nabiałek (Archives of Metallurgy and Materials, 2022)
Microstructures are an important link between materials processing and performance, and microstructure control is essential for any materials processing route where the microstructure plays a major role in determining the properties. In this work, silver-doped titanium dioxide (Ag/TiO2) thin film was prepared by the sol-gel method through the hydrolysis of titanium tetra-isopropoxide and silver nitrate solution. The sol was spin coated on ITO glass substrate to get uniform film followed by annealing process for 2 hours. The obtained films were annealed at different annealing temperatures in the range of 300°C-600°C in order to observe the effect on crystalline state, microstructures and optical properties of Ag/TiO2 thin film. The thin films were characterized by X-Ray diffraction (XRD), scanning electron microscopy (SEM), and UV-Vis spectrophotometry. It is clearly seen, when the annealing temperature increases to 500°C, a peak at 2θ = 25.30° can be seen which refers to the structure of TiO2 tetragonal anatase. The structure of Ag/TiO2 thin film become denser, linked together, porous and uniformly distributed on the surface and displays the highest cut-off wavelength value which is 396 nm with the lowest band gap value, which is 3.10 eV.